2018
DOI: 10.1021/acsami.7b18948
|View full text |Cite
|
Sign up to set email alerts
|

Designing Binary Ru–Sn Oxides with Optimized Performances for the Air Electrode of Rechargeable Zinc–Air Batteries

Abstract: Because of the sluggish kinetics of the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR), binary ruthenium-tin oxides synthesized by a hydrothermal method with postannealing at 450 °C for 2 h are first proposed as bifunctional catalysts for these two reactions on the air electrode of rechargeable zinc-air batteries. The binary Ru-Sn oxides in various compositions show the typical oxide solid solution in the rutile phase. Among all binary Ru-Sn oxides, RuSn73 (70 atom % RuO and 30 atom % SnO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 66 publications
0
36
0
Order By: Relevance
“…Figure (a) demonstrates that on the diffraction patterns of 2 % SnRuO‐IMP and 2 %SnRuO‐DP, a novel second phase is observed at 2θ=28.12° and 35.08° in addition to the SnO 2 phase, which can be attributed to the diffraction of (110) and (101) of RuO 2 crystalline phase on the catalyst surface. In contrast, for 2 %SnRuO‐CP samples, no RuO 2 crystalline phase can be observed, which implies that Ru 4+ cations could have entered into the rutile SnO 2 lattice matrix to form a solid solution structure ,. However, for the samples containing 5 % Ru loadings, the diffraction feature of RuO 2 crystalline phase is observed for all the catalysts.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…Figure (a) demonstrates that on the diffraction patterns of 2 % SnRuO‐IMP and 2 %SnRuO‐DP, a novel second phase is observed at 2θ=28.12° and 35.08° in addition to the SnO 2 phase, which can be attributed to the diffraction of (110) and (101) of RuO 2 crystalline phase on the catalyst surface. In contrast, for 2 %SnRuO‐CP samples, no RuO 2 crystalline phase can be observed, which implies that Ru 4+ cations could have entered into the rutile SnO 2 lattice matrix to form a solid solution structure ,. However, for the samples containing 5 % Ru loadings, the diffraction feature of RuO 2 crystalline phase is observed for all the catalysts.…”
Section: Resultsmentioning
confidence: 86%
“…Although individual RuO 2 or SnO 2 , are found to show activity for CO oxidation, RuO 2 −SnO 2 composite oxides have been rarely studied as catalysts for those air pollution control reactions up to now. People have shown main interest on using RuO 2 −SnO 2 as electrochemical materials, such as electrode, super‐capacitors and electrocatalysts . It has been reported that change of preparation methods can significant affect the structure and performance of RuO 2 −SnO 2 composite oxides.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations